IDEOLOGI KEMANUSIAAN DALAM PENDIDIKAN AGAMA ISLAM - Mukhamad Saekan (Edukasia: Jurnal Penelitian Pendidikan Islam, 2017)
THE IDEOLOGY OF HUMANITY IN ISLAMIC EDUCATION.Undang Undang Sistem Pendidikan Nasional (UUSPN) Number 20 of 2003 explains that one of the main goals of education is that learners have spiritual and religious strength and noble character. It shows how important the position of Islamic education in the context of national education. In addition, the formulation of education contains clearly about humanity aspects that are implemented into the reality of social life so that the system of social life order created a sense of mutual respect, peace, harmony without any conflict among others. Therefore, the ideology of humanity is absolutely necessary to be implemented by the teachers (Guru PAI). This study will discuss at least three things: the understanding of Islamic Education, the understanding of humanity ideology and how to implement the ideology of humanity in Islamic education. In its implementation, the ideology of humanity can be done normatively and technically. Normatively can be done by having a proper point of view to the students in all aspects of education, technically can be done by applying some learning approaches such as active learning, cooperative learning, and fun learning.